2013
DOI: 10.21608/asat.2013.22181
|View full text |Cite
|
Sign up to set email alerts
|

Flutter and Divergence Characteristics of Composite Plate Wing

Abstract: In the present work, an analytical investigation is introduced to determine the aeroelastic behavior of unswept, rectangular wings simulated by cantilevered composite plates using energy formulation and incompressible aerodynamic theory. Modified higher order shear deformation theory is used in the structural formulation. Doublet point method is used to solve the subsonic unsteady flow over the proposed rectangular wing. The flutter and divergence velocities are obtained using U-g method, which are validated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…where, (26) In this study, the composite plate is considered as a thin plate where the panel is divided into several boxes for aerodynamics modelling. The thin composite panel is divided equally into 20 boxes in the spanwise direction and 5 boxes in the chordwise.…”
Section: Doublet Lattice Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where, (26) In this study, the composite plate is considered as a thin plate where the panel is divided into several boxes for aerodynamics modelling. The thin composite panel is divided equally into 20 boxes in the spanwise direction and 5 boxes in the chordwise.…”
Section: Doublet Lattice Methodsmentioning
confidence: 99%
“…The same coupling procedure between DLM and structural modelling using modified higher order shear deformation theory was performed by Abbas et al [26] to estimate the flutter speed. There is another finite element that can be used, e.g.…”
Section: Aerostructural Couplingmentioning
confidence: 99%
“…The result of the study showed that composite layup orientation angles have played a great role which can be considered as a design parameter for the aero elastic instability analysis of on the wing flutter and divergence speeds. Modified higher order shear deformation theory for the structural computation and Doublet point method for the aerodynamic unsteady flow formulations were applied for the aeroelastic instability analysis [24]. The researchers used U-g method for flutter and divergence velocities estimations.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the former case include: Refs. [?, [9][10][11][12], which approximated composite lifting surfaces as cantilever plates and optimised for aeroelastic stability, neglecting the effects on structural weight; and Refs. [3,7,[13][14][15][16], which used wing-box models, including skins, spar and ribs, in order to obtain a more accurate structural and aeroelastic performance characterisation.…”
Section: Introductionmentioning
confidence: 99%